Structure of F1-ATPase from the obligate anaerobe Fusobacterium nucleatum. Issue 6 (26th June 2019) - Petri, Jessica; Nakatani, Yoshio; Montgomery, Martin G.; Ferguson, Scott A.; Aragão, David; Leslie, Andrew G. W.; Heikal, Adam; Walker, John E.; Cook, Gregory M.
Abstract : Abstract : The crystal structure of the F1 -catalytic domain of the adenosine triphosphate (ATP) synthase has been determined from the pathogenic anaerobic bacterium Fusobacterium nucleatum . The enzyme can hydrolyse ATP but is partially inhibited. The structure is similar to those of the F1 -ATPases from Caldalkalibacillus thermarum, which is more strongly inhibited in ATP hydrolysis, and in Mycobacterium smegmatis, which has a very low ATP hydrolytic activity. The βE -subunits in all three enzymes are in the conventional 'open' state, and in the case of C. thermarum and M. smegmatis, they are occupied by an ADP and phosphate (or sulfate), but in F. nucleatum, the occupancy by ADP appears to be partial. It is likely that the hydrolytic activity of the F. nucleatum enzyme is regulated by the concentration of ADP, as in mitochondria.